The representativeness of observational samples of different durations. - Mudford, O C (1990)
The representativeness of behavioral observation samples with durations of less than the whole time of interest was investigated. A real-time recording system was developed to quantify the behavior of 5 profoundly mentally retarded physically handicapped adult students in an institutional training setting. Behavior was observed using six mutually exclusive and exhaustive categories during 2.5-hr observation sessions. Sample observation sessions with durations ranging from 15 to 135 min were computer simulated from the whole-session (150-min) records. It was found that the representativeness of these samples, when compared to whole-session records, was a function of the relative duration of the behavioral categories and of sample duration. The occurrence of relatively high-duration behaviors (lasting for more than 50% of the session) was estimated to within 20% error by samples of less than 60 min, but low-duration behaviors (1 to 3% of the session) were inadequately quantified even from 135-min samples. Increasing irregularity of bouts of behavior in the low-duration behaviors is suggested as the cause of the functions obtained. Implications of the findings for applied behavior analysis are discussed, with the recommendation that the adequacy of observational session durations be empirically assessed routinely.